D&N Energy Enterprise / Nurul Jannatul Naimah Ibrahim - Ibrahim, Nurul Jannatul Naimah (2020)
Regarding to fulfil Fundamental of Entrepreneurship (ENT300) course requirement, we need to carry out a case study. During a case study, I need collect all information about a company to complete study case, so I decided to contact D&N Energy Enterprise manager who is Puan Nor Ismawati binti Ismail. From the interview I have known about their background of the business organizational structure, type of business model, products or services marketing and operational strategy. Besides that, I also enable to analyses the business entity using SWOT through case study and we need identify the problem that faced by their company and trying to recommend an alternative solution towards the problem.